Beneficial and adverse effects of vitamin E on the kidney - Baltusnikiene, Aldona; Staneviciene, Inga; Jansen, Eugène (Frontiers in Physiology, 2023)
This article has reviewed the beneficial and adverse effects of the vitamin E status and high dose supplementation with vitamin E, with an emphasis on renal effects in human and rodent studies. The metabolism of vitamin E in the kidney E has also been described. The renal effects caused by high doses of vitamin E were compared to upper limits of toxicity (UL) as established by various authorities worldwide. In recent mouse studies with higher doses of vitamin E, a number of biomarkers of tissue toxicity and inflammation were significantly elevated. In these biomarker studies, both the severity and the increased levels of the biomarkers will be discussed and whether the ULs may need to be re-evaluated given the toxic effects of vitamin E on the kidney with an emphasis on oxidative stress and sex differences. Finally, we sought to determine a dose range for vitamin E that has beneficial effects for healthy people and patients with renal diseases, yet is still save to avoid adverse effects.